2007
DOI: 10.1097/01.olq.0000258318.99606.d9
|View full text |Cite
|
Sign up to set email alerts
|

Condom Use and Vaginal Y-Chromosome Detection: The Specificity of a Potential Biomarker

Abstract: Condom use during intercourse appears to prevent vaginal YCS detection; this may be a useful biomarker to validate self-reported condom use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 22 publications
1
36
0
Order By: Relevance
“…Other studies have demonstrated the validity of the Y chromosome for similar purposes. Molecular detection of the Y chromosome has been shown to be a valid biomarker of semen in the vaginal vault [10,11,21]. Y-chromosome can be detected for a longer time period after unprotected intercourse compared to PSA (14 vs. 2 days).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies have demonstrated the validity of the Y chromosome for similar purposes. Molecular detection of the Y chromosome has been shown to be a valid biomarker of semen in the vaginal vault [10,11,21]. Y-chromosome can be detected for a longer time period after unprotected intercourse compared to PSA (14 vs. 2 days).…”
Section: Discussionmentioning
confidence: 97%
“…However, Thomsen et al [17] reported that knowledge of testing for semen exposure did not affect research participants' answers related to unprotected sex. Second, we used face-to-face interviews to collect self-report condom use data, a method known to increase reporting bias [21]. Third, we did not limit our study to recent intercourse (with or without using condom).…”
Section: Discussionmentioning
confidence: 99%
“…Yc is a predictor of recent unprotected sexual activity [1][2][3][4][5][6][7][8] and CV samples from women at high risk of STIs have frequently been found to contain traces of semen [33].…”
Section: Discussionmentioning
confidence: 99%
“…The estimated specificity is 92 % (95 % CI (80, 98)): i.e., 92 % of women in the calibration trial who had protected sex tested negative for Yc-PCR, and the 8 % of women each had digital or oral genital contact by their male partner, so the false positives could be explained by epithelial cells. [28][29][30] Participants were paid $50 upon completion of each survey. Emory University's Institutional Review Board approved the study protocol prior to implementation.…”
Section: Sample and Proceduresmentioning
confidence: 99%
“…We chose a measure of unprotected sex that most strongly predicted subsequent pregnancy according to a measure of effect size. Unprotected sex was coded as 1 for respondents who met one of the following criteria: positive test on a biomarker for semen exposure in the last 2 weeks 29,30 , self-report of no condom use in the past 14 days, or self-report of no current oral contraception use. This measure was chosen because it was the strongest predictor of pregnancy in the subsequent wave 6 months later: Cohen's effect size of d = 0.17 for wave 2 pregnancy and d = 0.10 for wave 3 pregnancy (Appendix Table 6).…”
Section: Measures Outcomes: Pregnancy and Pregnancy Preventionmentioning
confidence: 99%